F(-2)=6-2x

Simple and best practice solution for F(-2)=6-2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for F(-2)=6-2x equation:



(-2)=6-2F
We move all terms to the left:
(-2)-(6-2F)=0
We add all the numbers together, and all the variables
-(-2F+6)+(-2)=0
We add all the numbers together, and all the variables
-(-2F+6)-2=0
We get rid of parentheses
2F-6-2=0
We add all the numbers together, and all the variables
2F-8=0
We move all terms containing F to the left, all other terms to the right
2F=8
F=8/2
F=4

See similar equations:

| 0.5(3x+2)=0.25 | | 5x+17=−7(x+1) | | 2^4*2^-6=2^n | | 6x+29=−97−3x | | X^2x-32=4x | | 2x+(x+8)+2x=90 | | 3x+8+x=2+2x | | 2x(3)=12 | | z/5+2=-85 | | -4+6x=-42 | | (2x+15)+(2x+5)+(4x)=180 | | x=479 | | -5(c-2)=20-5c+20+10 | | 6(7+x)+5x=-35 | | (3b-2)/5=2 | | -89=5n-4 | | 1.25/5=x/3 | | m/14-3=m-302/84 | | (3b-2)/5=2 | | 10+4.25x=1+5.75x | | |4x|+16=8 | | -3/7=3/4-1x/2 | | 4x5=-17 | | 3x^2=12x-4 | | u+3.8=9.14 | | 2/3(-6x-3)=x-(-6x)+4+5x | | 0.63x+7=0.84x | | 4-6x-2=-2(3x1 | | –4w=2−5w | | 5-(7-4d)=12d | | 2(w–6)=3ww= | | 7x+11=4x-2x+26 |

Equations solver categories